Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Exploring the complex relationship between vestibular symptoms and migraine: a resting‑state functional MRI study - Lin Han; Xing Xiong; Jiajie Lu; Kai Zhang; Jun Ke; Hongru Zhao (Brain Imaging and Behavior, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ce-Fe-MI/CA composite catalyst for catalytic ozonation: Synergistic adsorption-activation via Ce/Fe sites & oxygen vacancies and application in air flotation-catalytic ozonation coupling process for pharmaceutical wastewater - Lin Yue; Shiqi Xing; Xiaoyun Han; Wang Liang; Yanfang Liu; Xinyang Liang; Yonghui Han (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pathway toward carbon neutrality of cement industry: A comprehensive analysis based on microdata - Mengling Zhang; Baokun Li; Hairui Yang; Man Zhang; Dongfang Li; Xing Zhu; Runsheng Lin; Yongkang Han; Aoyang Zhang (Fuel, 2026)

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Agglomeration of coal gangue particles in an ultra-supercritical CFB boiler: microstructure, thermodynamic modeling, mechanisms and prevention methods - Xiuting Yang; Junjie Li; Seokgi Ahn; Yongkang Han; Lin Pu; Chung-Hwan Jeon; Hua Wang; Xing Zhu; Tao Zhu; Dongfang Li (Fuel, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Chemical characteristics and source apportionment of free amino acids in the Qinling forest atmosphere of central China - Xin Zhang; Rui Wang; Jianjun Li; Shuyan Xing; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Atmospheric Environment, 2026)

Tannic acid-mediated oxygen vacancies in broccoli-like CeO2@Carbon for enhanced photocatalytic peroxymonosulfate activation toward tetracycline degradation - Huage Lin; Xinrui Han; Yihan Tang; Jiaxiang Zong; Guangyu Wu; Weinan Xing (Environmental Research, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Interfacial charge modulation in CuFe2O4/MXene composites: Enhancing persulfate activation and efficient degradation of chloroquine phosphate - Yeqiong Huang; Zhi Song; Boxia Liu; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Journal of Environmental Chemical Engineering, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Molecular characteristics of brown carbon aerosols over a forest atmosphere in the Qinling region of central China - Xin Zhang; Shuyan Xing; Jianjun Li; Rui Wang; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Environmental Pollution, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Feasibility of one-step nanofiltration driven by ultra-low pressure (LPOSNF) for algae-laden brackish water treatment: insights from the relationship between algal physiological state and membrane fouling development - Dachao Lin; Zhongjian Zhuang; Hualong Zhao; Yi Wu; Xiaobin Ma; Zhihong Wang; Han Zhang; Lifan Liu; Xing Du (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Correction: Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Interinterface electron-proton co-engineering: The dual regulation of surface charge and hydroxylation promotes the efficient activation and degradation of chloroquine phosphate by monopersulfate - Zhi Song; Yeqiong Huang; Boxia Liu; Hongqiao Jiao; Yulong Ma; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Chemical Engineering Journal, 2025)

Heteroatom- and bonded tailored Schottky barrier in Ti₃C₂ MXene/carbon nitride heterojunctions toward efficient photocatalysis - Weinan Xing; Huage Lin; Weifan Shao; Ning Jian; Teng Liu; Shanpeng Wen; Jiangang Han; Guangyu Wu (Chemical Engineering Journal, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

Spatial adaptations in hospitality amid COVID-19: A case study of Xiamen's B&B sector - Juan Lin; Han Li; Shuyu Xing; Weiye Xiao (Applied Geography, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

A novel gravity-driven fixed-bed ceramic membrane filtration (GDFBCM) with critical PAC-MnOx-ceramsite filters for simultaneously removing hazardous manganese and ammonia from groundwater - Dachao Lin; Zhitian Peng; Xiaopeng Zhang; Zhihong Wang; Yi Wu; Xiaobin Ma; Han Zhang; Wei Song; Lifan Liu; Jinxu Nie; Xing Du (Journal of Hazardous Materials, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Establishing electro-functionalized gravity-driven ceramic membrane filtration (EGDCM) for decentralized treatment of algae-laden brackish water: Comparison of in-situ electro-oxidation and ex-situ electro-coagulation - Dachao Lin; Xinxu Shen; Caiwei Tan; Han Zhang; Rui Chen; Xing Du; Heng Liang (Water Research, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Fabrication of Ag based Surface Enhanced Raman Scattering substrates with periodic mask arrays by electron beam deposition - Tian Xing; Jiawei Wang; Jiaqing Wei; Xingxing Du; Ruijin Hong; Chunxian Tao; Qi Wang; Hui Lin; Zhaoxia Han; Dawei Zhang (Analytica Chimica Acta, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Well Logging Stratigraphic Correlation Algorithm Based on Semantic Segmentation - Cai-zhi Wang; Xing-yun Wei; Hai-xia Pan; Lin-feng Han; Hao Wang; Hong-qiang Wang; Han Zhao (Applied Geophysics, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Corrigendum to “In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration” [Chem. Eng. J. 496 (2024) 154330] - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Construction of Covalent organic frameworks with bex topology for efficient photocatalytic hydrogen production - Lin Wang; Changzhi Han; Jingwen Pan; Shuo Li; Jia-Xing Jiang; Fengyun Guo; Shiyong Gao; Dongbo Wang; Yong Zhang (Chemical Engineering Journal, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Settlement transfer mechanism of CFG piles for strengthening high-speed railway subgrades induced by twin shield tunnelling undercrossing - Beiyu Wu; Xing-Tao Lin; Dong Su; Kaihang Han; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2024)

Neurotoxic effects induced by flunitrazepam and its metabolites in zebrafish: Oxidative stress, apoptosis, and histone hypoacetylation - Yingjun Qin; Yajing Huang; Wenting Lin; Rui Huang; Kan Li; Xing Han; Yuan Ren (Science of The Total Environment, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

A resilience assessment framework for existing underground structures under adjacent construction disturbance - Kaihang Han; Dongmei Zhang; Xiangsheng Chen; Dong Su; Jiann-Wen Woody Ju; Xing-Tao Lin; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Flunitrazepam induces neurotoxicity in zebrafish through microbiota-gut-brain axis - Wenting Lin; Kan Li; Yingjun Qin; Xing Han; Xiaohui Chen; Yuan Ren (Science of The Total Environment, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

New furofuran and tetrahydrofuran lignans from the flower buds of Magnolia biondii Pamp and their antiallergic effects - Xing Zhang; Xi-Min Wu; Lin-Hang Han; Fei Qian; Liu-Qiang Zhang; Yi-Ming Li (Natural Product Research, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Soil bacteria respond intensely to resource limitations regulated by edaphic properties during secondary succession on a semiarid abandoned farmland - Zekun Zhong; Xing Wang; Rentao Liu; Dejie Kong; Haojie Nie; Xinhui Han; Gaihe Yang; Lin Zhu (CATENA, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

Human platelet mitochondria improve the mitochondrial and cardiac function of donor heart - Zhi Jun Lin; Soomin Kim; Hui Xing Cui; Kyuboem Han; Hong Kyu Lee; Chun-Hyung Kim; Young Cheol Kang; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Effects of Suspended Particles on Exopolysaccharide Secretion of Two Microalgae in Jinjiang Estuary (Fujian, China) - Jie Liu; Xiaoyu Han; Hui Xing; Yiting Nan; Jiahui Lin; Junming He; Sijia Chen; Yanfang Wei; Peiyong Guo (Journal of Marine Science and Engineering, 2022)
The effects of suspended particles (SP) of different concentrations and sizes on the secretion of exopolysaccharide (EPS) by Chlorella pyrenoidosa (C. pyrenoidosa) and Microcystis flos-aquae (M. flos-aquae) in Jinjiang Estuary, Fujian Province, China were studied in co-cultures of microalgae and SP. The results show that the SP concentration has an “inhibit–promote–inhibit” effect on the secretion of EPS by C. pyrenoidosa, whereby there is an optimal concentration of SP corresponding to the largest amount of EPS secreted by C. pyrenoidosa. Low concentrations had no significant effect on the secretion of EPS from M. flos-aquae (p > 0.05), whereas higher concentrations had an inhibitory effect. The C. pyrenoidosa EPS content was found to be significantly decreased in response to SP of small particle sizes (0–75 and 75–120 μm) and significantly increased for SP of large particle sizes (120–150 and 150–500 μm). Small particle sizes (0–75 and 75–120 μm) were found to be beneficial to the secretion of EPS from M. flos-aquae, and the promotion of EPS secretion gradually decreased with the increase in SP particle size. However, when the particle size was too large (120–150 and 150–500 μm), SP had no significant effect on EPS secretion. This study is helpful for understanding the microalgae EPS secretion response to SP and provides a scientific basis for studying the mechanism of EPS secretion by algae and the effect of SP on eutrophication of the estuary.

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Climate factors during key periods affect the comprehensive crop losses due to drought in Southern China - Qiang Zhang; Lanying Han; Jian Zeng; Xing Wang; Jingjing Lin (Climate Dynamics, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

Bin-based genome-wide association analyses improve power and resolution in QTL mapping and identify favorable alleles from multiple parents in a four-way MAGIC rice population - Zhongmin Han; Gang Hu; Hua Liu; Famao Liang; Lin Yang; Hu Zhao; Qinghua Zhang; Zhixin Li; Qifa Zhang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Phenolic acid production is more effectively enhanced than tanshinone production by methyl jasmonate in Salvia miltiorrhiza hairy roots - Bingcong Xing; Dongfeng Yang; Lin Liu; Ruilian Han; Yanfang Sun; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Evaluation of Flow Velocity in Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Lin Wang; Yingqi Xing; Yang Li; Ke Han; Jiafeng Chen (Cell Biochemistry and Biophysics, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)